Tumor-Specific Antibody, Cetuximab, Enhances the In Situ Vaccine Effect of Radiation in Immunologically Cold Head and Neck Squamous Cell Carcinoma - Jin, Won Jong; Erbe, Amy K.; Schwarz, Ciara N.; Jaquish, Abigail A.; Anderson, Bryce R.; Sriramaneni, Raghava N.; Jagodinsky, Justin C.; Bates, Amber M.; Clark, Paul A.; Le, Trang; Lan, Keng-Hsueh; Chen, Yi; et al. (Frontiers in Immunology, 2020)
In head and neck squamous cell carcinoma (HNSCC) tumors that over-expresses huEGFR, the anti-EGFR antibody, cetuximab, antagonizes tumor cell viability and sensitizes to radiation therapy. However, the immunologic interactions between cetuximab and radiation therapy are not well understood. We transduced two syngeneic murine HNSCC tumor cell lines to express human EGFR (MOC1- and MOC2-huEGFR) in order to facilitate evaluation of the immunologic interactions between radiation and cetuximab. Cetuximab was capable of inducing antibody-dependent cellular cytotoxicity (ADCC) in MOC1- and MOC2-huEGFR cells but showed no effect on the viability or radiosensitivity of these tumor cells, which also express muEGFR that is not targeted by cetuximab. Radiation enhanced the susceptibility of MOC1- and MOC2-huEGFR to ADCC, eliciting a type I interferon response and increasing expression of NKG2D ligands on these tumor cells. Co-culture of splenocytes with cetuximab and MOC2-huEGFR cells resulted in increased expression of IFNγ in not only NK cells but also in CD8+ T cells, and this was dependent upon splenocyte expression of FcγR. In MOC2-huEGFR tumors, combining radiation and cetuximab induced tumor growth delay that required NK cells, EGFR expression, and FcγR on host immune cells. Combination of radiation and cetuximab increased tumor infiltration with NK and CD8+ T cells but not regulatory T cells. Expression of PD-L1 was increased in MOC2-huEGFR tumors following treatment with radiation and cetuximab. Delivering anti-PD-L1 antibody with radiation and cetuximab improved survival and resulted in durable tumor regression in some mice. Notably, these cured mice showed evidence of an adaptive memory response that was not specifically directed against huEGFR. These findings suggest an opportunity to improve the treatment of HNSCC by combining radiation and cetuximab to engage an innate anti-tumor immune response that may prime an effective adaptive immune response when combined with immune checkpoint blockade. It is possible that this approach could be extended to any immunologically cold tumor that does not respond to immune checkpoint blockade alone and for which a tumor-specific antibody exists or could be developed.